RUG3 is a negative regulator of plant responses to ABA in Arabidopsis thaliana - Su, Chao (Plant Signal Behav, 2017)
Mitochondria is a main target of various stressors. Dysfunction of mitochondria stimulates overproduction of reactive oxygen species (ROS), which can cause oxidative damage to mitochondria and DNA. Recently, we demonstrated that RCC1/UVR8/GEF-like 3 (RUG3), a member of the Regulator of Chromatin Condensation 1 (RCC1) protein family, can directly interact with ataxia telangiectasia mutated (ATM), a key regulator of the DNA damage response (DDR), and synergistically regulates the alternative splicing of mitochondrial nad2. Aberrant ROS accumulation and mitochondrial dysfunction result in root growth retardation and increased DDR. Here we reveal that RUG3 mutations increased plant responses to ABA during seed germination and post-germinative growth. Our findings identify RUG3 as a novel regulator of ABA signaling pathway in Arabidopsis thaliana.